Dynamic EROI Assessment of the IPCC 21st Century Electricity Production Scenario - Charles Neumeyer (Sustainability, 2016)
The Energy Return on Investment (EROI) is an important measure of the energy gain of an electrical power generating facility that is typically evaluated based on the life cycle energy balance of a single facility. The EROI concept can be extended to cover a collection of facilities that comprise a complete power system and used to assess the expansion and evolution of a power system as it transitions from one portfolio mix of technologies to another over time. In this study we develop a dynamic EROI model that simulates the evolution of a power system and we perform an EROI simulation of one of the electricity production scenarios developed under the auspices of the Intergovernmental Panel on Climate Change (IPCC) covering the global supply of electricity in the 21st century. Our analytic tool provides the means for evaluation of dynamic EROI based on arbitrary time-dependent demand scenarios by modeling the required expansion of power generation, including the plowback needed for new construction and to replace facilities as they are retired. The results provide insight into the level of installed and delivered power, above and beyond basic consumer demand, that is required to support construction during expansion, as well as the supplementary power that may be required if plowback constraints are imposed. In addition, sensitivity to EROI parameters, and the impact of energy storage efficiency are addressed.